2009
DOI: 10.1007/s12028-009-9215-y
|View full text |Cite
|
Sign up to set email alerts
|

Sixty Day Continuous Use of Subdermal Wire Electrodes for EEG Monitoring During Treatment of Status Epilepticus

Abstract: Subdermal wire electrodes offer a safe method to overcome technical challenges while maintaining high-recording quality. Their advantages and disadvantages are considered in specific circumstances and in comparison to other electrode types.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…This would not involve invasive electrodes within the skull, but instead, electrodes placed below the scalp (subcutaneously or subdermally) essentially not externally visible and intrinsically held in place. A recent study has shown the use of subdermal electrodes in the intensive care unit continuously for 60 days [31].…”
Section: Electrode Technologymentioning
confidence: 99%
“…This would not involve invasive electrodes within the skull, but instead, electrodes placed below the scalp (subcutaneously or subdermally) essentially not externally visible and intrinsically held in place. A recent study has shown the use of subdermal electrodes in the intensive care unit continuously for 60 days [31].…”
Section: Electrode Technologymentioning
confidence: 99%
“…SWE are single use disposable Teflon-coated silver wire with a 3-5mm silver chlorided tip (Mirsattari, Lee et al 2004, Ives 2005, Vulliemoz, Perrig et al 2009). They may reduce skin breakdown and provide superior recording characteristics compared to disc electrodes for patients requiring very prolonged CCEEG monitoring (Martz, Hucek et al 2009). They cause little artifact on CT and angiography and can be MRI compatible with specialized connectors.…”
Section: Cceeg Monitoring Equipmentmentioning
confidence: 99%
“…Prior modeling studies suggest that subdermal electrodes could provide accurate measurements CE signals (Subramaniyam et al, 2011). Clinical studies have been done to record low frequency oscillations with subdermally placed electrodes (Young et al, 2006, Martz et al, 2009), and Pfurtscheller and Cooper in 1975 showed frequency-dependent attenuation up to 30 Hz in humans. However, the signal properties of subdermal recording methods are still poorly understood, particularly the spectral transfer function of the HG signal as it passes through the skull.…”
Section: Introductionmentioning
confidence: 99%